Mitogenomics reveals two subspecies in Coelomactra antiquata (Mollusca: Bivalvia). (April 2013) - Meng, Xueping; Shen, Xin; Zhao, Nana; Tian, Mei; Liang, Meng; Hao, Jue; Cheng, Hanliang; Yan, Binlun; Dong, Zhiguo; Zhu, Xiaoling
<x xml:space="preserve">Abstract</x> The mitochondrial genome sequence of Coelomactra antiquata (Mollusca: Bivalvia) in Zhangzhou (zz-mtDNA) was fully sequenced and compared with that in Rizhao (rz-mtDNA) in this study. A tRNA (tRNAMet) located between tRNAAla and cox1 genes was identified in zz-mtDNA but not in rz-mtDNA. The largest non-coding region (NCR; MNR) contained 11 copies 99nt tandem repeat sequences exclusively in rz-mtDNA, while the second largest NCR with 400 bp between tRNAAla and tRNAMet in zz-mtDNA was absent in rz-mtDNA. Secondary structures of ZZ and RZ C. antiquata rRNAs are significantly different. The mitochondrial genomic characteristics clearly indicate that there are at least two subspecies in C. antiquata.